Improved age tie points based on the benthic δ18O records in the upper part of the Kiwada Formation - Daisuke Kuwano; Koji Kameo; Yoshimi Kubota; Utsunomiya Masayuki; Kanako Mantoku; Makoto Okada (PANGAEA, 2024)
The improved age tie points based on the benthic δ18O records in the upper part of the Kiwada Formation. The age of Sample A0926-02 was modified from Kuwano et al. (2021).
In: Kuwano, D et al. (2024): Early Pleistocene (marine isotope stage 36–40) calcareous nannofossil assemblage data from the upper part of the Kiwada Formation, the Kazusa Group [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.971412